دراسة أثر سماكة البطانة القرميدية و الفراغ الهوائي و القشرية البيتونية على العزوم الناجمة عن التأثيرات الحرارية في جدران المداخن البيتونية الصناعية - زكائي طريفي; يارا رستم (Tishreen University, 2018)
The concrete industrial chimneys are considered one of most important structures in regard to industrial as well as environmental fields  to get rid of detrimental gases which are produced according to industrial operations. they are also considered a first instruments to send these undesired gases to higher atmosphere levels, that lead to mitigate their pollution. In this paper we have studied the effects of changing the thickness of  brick lining and concrete wall in addition to the air gap effect on the thermal moments in chimneys wall and we recommended an optimal thickness for all of them that achieve best effectiveness in order to mitigate thermal effect in chimneys walls . we have used one of Banias refineries as primary model for this research. We concluded that air gap existence give a big effect on thermal moments reduction and increasing the gap thickness will not give any marked effect. But increasing the concrete wall thickness will play a negative role on the concrete wall thermal moments . Brick layer has a positive effect but in just a particular ranges that achieves optimal insulation and  economic benefit . تعد المداخن البيتونية الصناعية من المنشآت الهامة من الناحية الصناعية والبيئية للتخلص من الغازات الضارة الناجمة عن العمليات الصناعية حيث تعد الوسيلة الأولى لتصريف هذه الغازات الى طبقات الجو العليا مما يؤدي إلى تخفيف التلوث الناجم عن هذه الغازات. تم في هذا البحث دراسة أثر تغيير سماكة البطانة القرميدية و سماكة القشرية البيتونية بالإضافة إلى إيجاد أثر الفراغ الهوائي في المدخنة على العزوم الحرارية في جدران المدخنة و اقتراح السماكة الأمثل لكل منها التي تحقق الفعالية الأكبر في تخفيف الأثر الحراري في جدار المدخنة, حيث تم الاستفادة من مدخنة مصفاة بانياس كنموذج افتراضي للدراسة. تم الاستنتاج أن وجود الفراغ الهوائي يعطي أثر كبير في انخفاض العزم الحراري في جدار المدخنة و أن زيادة سماكة هذا الفراغ لا تعطي أثر ملحوظ في حين أن لزيادة سماكة القشرية أثر سلبي على العزم الحراري في الجدران, أما البطانة القرميدية فلها أثر إيجابي ضمن حدود معينة تحقق العزل الأمثل و الوفر الاقتصادي.